Single therapeutic dose of an antiviral UL29 siRNA swarm diminishes symptoms and viral load of mice infected intranasally with HSV-1 - Lasanen Tuomas; Frejborg Fanny; Lund Liisa M.; Nyman Marie C.; Orpana Julius; Habib Huda; Alaollitervo Salla; Levanova Alesia A.; Poranen Minna M.; Hukkanen Veijo; Kalke Kiira (Wiley, 2025)
Herpes simplex virus type 1 (HSV-1) is a human pathogen that causes recurrent infections. Acyclovir-resistant strains exist and can cause severe complications, which are potentially untreatable with current therapies. We have developed siRNA swarms that target a 653 base pair long region of the essential HSV gene UL29. As per our previous results, the anti-UL29 siRNA swarm effectively inhibits the replication of circulating HSV strains and acyclovir-resistant HSV strains in vitro, while displaying a good safety profile. We investigated a single intranasal therapeutic dose of a siRNA swarm in mice, which were first inoculated intranasally with HSV-1 and given treatment 4 h later. We utilized a luciferase-expressing HSV-1 strain, which enabled daily follow-up of infection with in vivo imaging. Our results show that a single dose of a UL29-targeted siRNA swarm can inhibit the replication of HSV-1 in orofacial tissue, which was reflected in ex vivo HSV titers and HSV DNA copy numbers as well as by a decrease in a luciferase-derived signal. Furthermore, the treatment had a tendency to protect mice from severe clinical symptoms and delay the onset of the symptoms. These results support the development of antiviral siRNA swarms as a novel treatment for HSV-1 infections.